Artificial Intelligences, Robots, Bio-engineering and Cyborgs: New Challenges for Theology? - Benanti, Paolo (Concilium, 2019)
Looking at the great transformations that this new stage of technology is producing, I ask if these 'new artefacts 'are simply instruments or perhaps also 'sites' of our life that demand new anthropological and theological reflection. To do this 1 shall first introduce some new artefacts that seem to be key elements of these transformations and secondly I shall try to bring out some of the questions or issues the achievements of these technologies presents to philosophical and theological investigation. The conclusions seek to highlight how, in order to engage with the challenges technology confronts us with, we must first understand it not only as an instrument but also as a theological 'site'. In order to live in today's world we are called upon to reformulate the truths of the faith in a way that allows them to illuminate and give meaning to these 'new artefacts 'and the challenges these present. We are called upon to think theologically about technology also to understand more deeply the mystery of God and the human vocation. In addition, technological developments on these unexplored frontiers requires more than ever today interdisciplinary debates and contributions, including those of theology, if we are tofind adequate ends for the innumerable means it has at its disposal.